Pressuremeters proceedings of the Third International Symposium on Pressuremeters, organised by the British Geotechnical Society and held at Oxford University, 2-6 April 1990. (Thomas Telford, 1990)
The technology, data interpretation and applications of pressure meters have progressed rapidly. Covering the design and construction of pressure meters, this text also discusses their uses, including developments in the field.